Impact of non-linear radiation on magneto - Casson fluid suspended hybrid nanomaterials in sodium alginate: Smarter textiles - P. Sreenivasulu; T. Poornima; Basma Souayeh (Hybrid Advances)
Background: The combination of sodium alginate (SA) and nanoparticles in Casson nanofluids can have several advantages in textile applications such as to enhance the dye absorption and finishing properties and uniform and controlled coatings on complex shapes of the fabric and garments with intricate designs or three-dimensional textile structures etc. These fascinating properties attracted us to work on this article, a Casson hybrid nanoflow under the influence of magnetic effects past a curved stretching surface. Key terms & problem definition: This study examines the heat transfer characteristics of Casson nanofluid flow over a stretching sheet with nonlinear thermal radiation and convective boundary conditions. A Casson fluid is a non-Newtonian fluid that exhibits a yield stress, meaning it behaves like a solid below a certain shear stress. Nonlinear thermal radiation accounts for the effects of temperature-dependent radiative heat transfer. Convective boundary conditions simulate the heat exchange between the fluid and a surrounding environment. The nanoflow has its base fluid as Sodium Alginate (SA) and a mixture of Silver (Ag) and Titanium oxide (TiO2) is suspended in the fluid. Methodology: The nanoflow model is cracked numerically employing Runge-Kutta Fehlberg technique along with shooting method. Results of flow affecting parameters on the flow characteristic quantities and engineering quantities are portrayed and presented through graphs and tables. Key findings: Hybrid Nanoflow momentum decreases with an increase in the Casson parameter due to the yield stress which quite helps in the controlled and complex shape printing on the garments. The temperature of the nanofluid increases with an increase in nonlinear radiation parameter. In the presence of Ag and TiO2 nanoparticles, the non-linear radiation parameter becomes essential for managing their intricate impact on heat transfer within the fabric. Practical relevance: Improved heat transfer can significantly reduce drying times, leading to increased productivity. More efficient heat transfer can reduce energy consumption. Reduced viscosity can allow for better penetration of fluids into fabrics, leading to more uniform dyeing and finishing. Casson hybrid nanofluids can accelerate the dyeing process and improve colour uniformity. Casson hybrid nanofluids can be used in finishing processes to enhance wrinkle resistance and improve fabric appearance.